Adsorption of Cationic Malachite Green Dye using Easily Separated Adsorbent of Magnetized Coal Fly Ash - Romadhona, Miftakhul; Aprilita, Nurul Hidayat; Mudasir, Mudasir (Molekul, 2024)
A study on the synthesis of magnetized adsorbents from coal fly ash (FA) for the adsorption of malachite green (MG) dye has been conducted. The method involves acid activation and ferrite magnetization of FA. The activation of FA was performed by mixing it in an HCl solution, while the magnetization was carried out by the coprecipitation method using the molar ratio of 1:2 of Fe2+/Fe3+. The magnetized coal fly ash adsorbent (FA/Fe3O4) was then utilized to adsorb the MG dye, and the results were compared with that adsorbed by activated fly ash (AFA). Characterization of the materials was carried out using Atomic Absorption Spectroscopy (AAS), Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), and Vibrating Sample Magnetometer (VSM). The optimized parameters in the adsorption study were pH, adsorbent mass, contact time, and initial concentration. The optimum conditions for the adsorption of MG dye with AFA and FA/Fe3O4 are obtained at pH 7, the adsorbent mass of 0.1 and 0.25 g respectively, a contact time of 45 minutes, and the initial concentration of MG dye of 175 ppm. The MG adsorption on both adsorbents follows a pseudo-second-order kinetic model and can be best described by the Langmuir isotherm adsorption model. The synthesized adsorbent is prospective as it is low cost and easily separable from the solution using an external magnet after adsorption. Keywords: Adsorption, coal fly ash, magnetite, malachite green